Thomas Kilroy’s Double Cross: Mediatized Realities and Sites of Multiple, Projected Selves - Jordan, Eamonn (FOCUS: Papers in English Literary and Cultural Studies, 2004)
In Irish theatre various explorations of the concept of the doppelgänger can be found ranging from Brian Friel’s Philadelphia, Here I Come! (1964) to Frank McGuinness’s Observe the Sons o f Ulster Marching Towards the Somme (1985); in the former, Gar O’Donnell is irresolvably split between Public and Private, and in the latter, the division is between Elder and Younger Pyper, different versions of the same character, who embrace at the end of the play, as if a considerable cycle of destructive division has been brought partly to an end and falsifications surrendered temporarily. Their embrace has personal, political and tribal implications. In Marina Carr’s Portia Coughlan (1996), Portia is haunted by her dead twin, Gabriel. The opening stage direction reads: “They mirror one another’s postures and movements in an odd way” (193). Such is their connection, however symbolic, real or spurious one believes it to be, she kills herself, unable to evade his death call. In Double Cross, a play produced by Field Day, Thomas Kilroy reflects on two men, Brendan Bracken—Minister for Information from 1941-45 in the Churchill government during the Second World War and the Nazi broadcaster William Joyce—better known as Lord Haw Haw. Both disaffected Irishmen were played by Stephen Rea (a co-founder of Field Day) in the play’s original production.